Metal atom (Zn, Cd and Mg) luminescence in solid neon - Healy, B.; Kerins, P.; McCaffrey, J. G. (Физика низких температур, 2012)
Luminescence spectroscopy of the metal atoms Mg, Zn and Cd isolated in solid neon is recorded using
pulsed synchrotron radiation excitation of the ns¹ np¹ ¹P₁–ns² ¹S₀ resonance (n = 3, 4 and 5 respectively) transitions.
Two features, a dominant band and a red-shoulder, are identified in the UV absorption spectra of
Zn/Ne and Cd/Ne. Excitation of these features yields distinct emission bands with the red-shoulder absorption
producing the smaller, Stokes-shifted emission. Nanosecond decaytime measurements, made with the time
correlated single photon counting technique indicate the emission bands arise from the spin singlet ¹P₁ → ¹S₀
transition. Hence, it is concluded the duplication of absorption and emission features in the Cd/Ne and Zn/Ne
systems arises from metal atom occupancy in two distinct sites. In contrast, Mg/Ne luminescence consists of
single excitation and emission bands, indicative of occupancy in just one site. The occurrence of distinct photophysical
characteristics of the linewidths, Stokes shift and lifetimes in the Mg/Ne system, compared with
those recorded for Zn/Ne and Cd/Ne, is rationalised in terms of a different site occupancy for atomic Mg. Accurate
interaction potentials for the ground states of the M·Ne diatomics are used to analyse site occupancies
and interpret this contrasting behavior.